PENGUATAN KOMPETENSI GURU MERDEKA BELAJAR BERBASIS TEKNOLOGI DIGITAL DI SMP NEGERI 1 DOLOK PARDAMEAN - Siahaaan, Mungkap Mangapul; Sirait, Jumaria; Purba, Rudiarman; Sihombing, Santa R; Pasaribu, Sunggul; Sinaga, Asima Rohana (Community Development Journal : Jurnal Pengabdian Masyarakat, 2024)
Dolok Pardamean Nagori, Dolok Pardamean District, Simalungun Regency is one of several priority areas for villages assisted by the Community Service Program by HKBP Nommensen Pematangsiantar University. Dolok Pardamean District has two State Middle Schools and one Private Middle School. SMP Negeri 1 Dolok Pardamean as one of the state junior high schools in Dolok Pardamean District was greatly affected by post-pandemic learning loss and due to the limited use of digital technology in learning. This is demonstrated by school academic data reports which show a decline in achievement in the 2019/2020, 2020/2021, 2021/2022 academic years. This resulted in a decrease in the number of new students. The 2022/2023 academic year will be a tough challenge for SMP Negeri 1 Dolok Pardamean to improve the school's academic quality after Covid-19. The use and implementation of various online learning, implementation of the Merdeka Belajar curriculum and strengthening digital-based teacher competency are programs prepared to be able to increase the skills of teachers at SMP Negeri 1 Dolok Pardemean so that as educational agents, SMP Negeri 1 Dolok Pardemean teachers are able to increase their interest and each student's interest in learning, innovation, creation and collaboration of competencies so that they work together to improve the academic, psychological and character quality of students. After understanding and mapping the problems at SMP Negeri 1 Dolok Pardamean, lecturers at the English Education Study Program, Mathematics Education Study Program, and Computer Science Study Program at HKBP Nommensen University Pematangsiantar determined and prioritized service to this school with the aim of strengthening the competence of teachers in terms of the curriculum. independent learning and digital technology-based learning. In terms of teacher competency, teachers will be trained in the steps to create and use various digital technology-based independent curriculum learning models and media. The solution is to hold a systematic strengthening and training program.